2016
DOI: 10.1080/20550340.2016.1260900
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the out-of-plane-permeability of preforms manufactured by dry fiber placement

Abstract: Dry fiber placement (DFP) is a technology which enables outstandingly high mechanical performance of composite parts as preform structures with load-related fiber orientations can be created with minimum of fiber crimp. Furthermore, DFP has high cost-saving potential due to minimum material wastage during production. Recently, the efficiency has been further improved using an online binder application system, allowing the direct usage of untreated rovings instead of pre-designed rovings with binder applied by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Recent work on permeability of dry tape preforms has focused on the experimental analysis by varying gap sizes, binder amounts, layup sequence, and tufting of preforms, in order to enhance the permeability [19,20]. However, no study has considered a detailed experimental and computational modelling approach for permeability predictions of AFP dry tape preforms.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Recent work on permeability of dry tape preforms has focused on the experimental analysis by varying gap sizes, binder amounts, layup sequence, and tufting of preforms, in order to enhance the permeability [19,20]. However, no study has considered a detailed experimental and computational modelling approach for permeability predictions of AFP dry tape preforms.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…This indicates that the binder was present within the material rather than on the surface, which could be the reason for its low bulk factor as well as a low permeability. Rimmel et al have already reported an influence of binder distribution on permeability (in this instance binder content and binder particle size), whereby the latter has greater influence [35]. The material that infused the preform fastest was Material A, which has the distinctive feature of a carbon fiber veil.…”
Section: Materials and Manufacturing Process Assessmentmentioning
confidence: 95%
“…Also, it is known that compared to woven fabrics or noncrimp fabrics (NCF) preforms made by DFP show a deficient impregnation behavior, which results from the lack of meso-flow channels (gaps between the fiber bundles) in the DFP preforms. To increase the permeability, tufting or a modified layup sequence (gaps between the rovings) is a promising approach [26,27].…”
Section: State Of the Artmentioning
confidence: 99%